Effect of Ethanolic Extract of Cinnamon (Cinnamomum burmannii) on Fasting Blood Glucose Levels in Alloxan- Induced Webster Mice - Cleo Aurelia Moza; Yanti Rosita; Rury Tiara Oktariza; Putri Erlyn (Faculty of Medicine, 2026)
Diabetes mellitus is a metabolic disorder with a globally increasing incidence; however, existing treatments remain limited by undesirable side effects and challenges in achieving optimal blood glucose levels. Natural products offer potential advantages, including lower toxicity profiles and the ability to modulate multiple metabolic pathways. Cinnamon is a natural ingredient known to contain various bioactive compounds with antidiabetic properties. This study aims to evaluate the effects of ethanol cinnamon extract (Cinnamomum spp.) on reducing fasting blood glucose (FBG) levels in alloxan-induced male Webster strain mice. An experimental method with a pre-post test control group design was employed. Five test groups were established: a negative control (distilled water), a positive control (metformin 1.3 mg), and three doses of cinnamon extract (150 mg/kg BW, 200 mg/kg BW, and 250 mg/kg BW). The results demonstrated that the administration of 200 mg/kg BW of cinnamon extract exerted an antihyperglycemic effect by significantly decreasing FBG levels in alloxan-induced mice (p